Assessing University and Programme Experiences: Towards an Integrated Asia Pacific Approach - Luke Kutszik Fryer (Frontiers Media S.A., 2021)
Effective assessment of university experiences is critical for quality assurance/enhancement but fragmented across the Pacific-Asian universities. A shared conceptual and measurement foundation for understanding student experiences is a necessary first step for inter-institutional communication across the region. The current study is a first step toward such a foundation, uniting two of the most internationally and locally prominent instruments: Chinese College Student Survey (university engagement; Mainland China) and Student Learning Experience Questionnaire (programme engagement; Hong Kong). The survey was completed by students from one research-intensive Hong Kong university (n = 539). Random, split-half CFA, latent-reliability, pair-wise correlations, ANOVA (gender) and MANOVA (faculty) were conducted. Factor-structure (good CFA fit for the test/retest) and scale reliability (0.07 > Raykov’s Rho) suggested a robust, short (63-items) survey resulted. Intra-/inter-survey relationships were consistent with the existing Student Engagement and Student Approaches to Learning theory. ANOVA indicated small differences for gender for a few latent constructs, but MANOVA revealed substantial differences across the 10 faculties. This study resulted in a robust Pacific-Asian intra-/inter-institutional student experience instrument which brings together two equally important perspectives on the student experience. This comprehensive student engagement instrument stands ready for cross-national and longitudinal tests. The new instrument’s benefits extend to theoretical connections to student experience assessment in the United States, Australia, and the United Kingdom enabling international connections to be made.